Clinical decision making : case studies in medical-surgical nursing - Ankner, Gina M.; Ahlschlager, Patricia M. ;Hale, Tammy J. (Australia : Delmar Cengage Learning, 2012)
Emphasizing holistic nursing care, this title bridges the gap between classroom knowledge and real-world practice.
1. The Cardiovascular System & the Blood -- 2. The Respiratory System. Asthma -- 3. The Nervous/Neurological System -- 4. The Sensory System -- 5. The Integumentary System -- 6. The Digestive System -- 7. The Urinary System -- 8. The Endocrine/Metabolic System -- 9. The Skeletal System -- 10. The Muscular System -- 11. The Reproductive System -- 12. Multi-System Failure
Includes index.
Keywords: NURSING -- CASE STUDIES